Local buckling of cantilever wall of thin-walled member with longitudinal and transverse stress variation - Szychowski, Andrzej (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
The paper presents results of the investigation into the stability of elastically restrained cantilever walls (plates) with longitudinal and transverse stress variation. A linear distribution of stresses in the direction of the wall (plate) width and the linear or nonlinear (in accordance with parabola 20) distribution of stresses along the wall length were assumed. Plots of plate buckling coefficients (k) for variously supported and variously loaded cantilever plates, which are not found in the literature, were determined.